Targeting Oxidative Stress and Aberrant Critical Period Plasticity in the Developmental Trajectory to Schizophrenia - Do, Kim Q. (Schizophr Bull, 2015)
Schizophrenia is a neurodevelopmental disorder reflecting a convergence of genetic risk and early life stress. The slow progression to first psychotic episode represents both a window of vulnerability as well as opportunity for therapeutic intervention. Here, we consider recent neurobiological insight into the cellular and molecular components of developmental critical periods and their vulnerability to redox dysregulation. In particular, the consistent loss of parvalbumin-positive interneuron (PVI) function and their surrounding perineuronal nets (PNNs) as well as myelination in patient brains is consistent with a delayed or extended period of circuit instability. This linkage to critical period triggers (PVI) and brakes (PNN, myelin) implicates mistimed trajectories of brain development in mental illness. Strategically introduced antioxidant treatment or later reinforcement of molecular brakes may then offer a novel prophylactic psychiatry.